Análise quanto a aplicação da autoria mediata pelo domínio da organização na administração de empresas - Lima, Otamiris Vale Caldas (2018)
Object of debate and constant research, the Theory of the Domain of the Fact was once again highlighted in the Brazilian legal scene at the time of the judgment of the Criminal Action 470 by the Federal Supreme Court. At that time, much questioned about its application and even severe criticisms were directed to that Court considering the inappropriate use of this theory. Notwithstanding the negative aspects, it can be said that such a circumstance has encouraged and brought back the employment of the theory of the domain of fact by all instances of judgment. And in truth, many are the contributions of the above-mentioned institute to criminal dogmatics, mainly in itself dealing with the correct application of the law as to the just distress and responsibility of the one who violated the norm. What is examined in this article, however, is the indiscriminate use to the detriment of this theory, including in the business sphere, as the title transpires. Therefore, we sought to aggregate several studies and current positions of authors who research on the subject; Claus Roxin himself, forerunner of the theory, has also expressed his position on such an imbroglio. In this way, and without pretensions to exhaust the subject, what is proposed is a frank analysis around the use of the theory of the domain of fact, as well as of its definition and all its subdivisions.